Shadow of a bull - Wojciechowska, Maia 1927-; Smith, Alvin (New York Atheneum, 1965)
Manolo Olivar has to make a decision: to follow in his famous father's shadow and become a bullfighter, or to follow his heart and become a doctor.
Newbery Medal Award
Keywords: Bullfights -- Fiction; Spain -- Fiction